Antoni van Leeuwenhoek : first to see microscopic life - Yount, Lisa. (Springfield, NJ : Enslow Publishers, 1996)
A biography of the cloth merchant-turned-scientist who made many discoveries examining microsopic life.
Includes bibliographical references (p. 125) and index.
Keywords: Leeuwenhoek, Antoni van, -- 1632-1723 -- Juvenile literature; Leeuwenhoek, Antoni van, -- 1632-1723.; Biologists -- Netherlands -- Biography; Microscopes -- History -- Juvenile literature; Biologists; Microscopes; Microscopy